Effectiveness of a low-cost gnss-rtk system to evaluate the performance of alpine skiing - Bortolan, L.; Nicolodi, M.; Callovini, A.; Todesco, B.; Schena, F. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Alpine skiing performance depends on a complex interaction between forces, energy dissipations, inter-dependency of turns, speed, and trajectories. Extensive studies have been done to understand the biomechanics of skiing. However, the necessary complexity of study approaches often limits the transferability of the testing procedures to field use. The present study investigates the effectiveness of using GNSS-RTK technology in evaluating the performance of alpine skiers.